2017
DOI: 10.5152/tjbh.2016.3357
|View full text |Cite
|
Sign up to set email alerts
|

Early Diagnosis of Lymphedema after Breast Cancer Treatment: Bio-Impedance Spectroscopy

Abstract: Objective: Breast cancer-related lymphedema is an important health problem. The aim of this study is to ensure early diagnosis of patients at risk of developing lymphedema and revealing the predisposing factors. Materials and Methods:Measurements in the pre-operative period and in postoperative months 3, 6, 9 and 12 and years 2 and 3 were performed prospectively with bio-impedance spectroscopy for patients treated for breast cancer between November, 2013 and November, 2016. Demographic and clinical-pathologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Specific characteristics of the 24 articles (23 studies) can be seen in Table 1. The majority of studies (83%, n 5 19) were observational, including one case-control, 38 nine prospective, [32][33][34][35][36][37][39][40][41] and nine retrospective 14,[42][43][44][45][46][47][48][49][50] cohort studies. Four studies were RCTs, 25,26,30,31 of which two studies used another surveillance program as a comparator.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Specific characteristics of the 24 articles (23 studies) can be seen in Table 1. The majority of studies (83%, n 5 19) were observational, including one case-control, 38 nine prospective, [32][33][34][35][36][37][39][40][41] and nine retrospective 14,[42][43][44][45][46][47][48][49][50] cohort studies. Four studies were RCTs, 25,26,30,31 of which two studies used another surveillance program as a comparator.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…42,45 Sensitivity analysis indicated that inclusion of these two studies in the pooled rates did not affect the results. The first postoperative assessment was performed within or at three months postsurgery in 20 studies (95%), 14,25,26,30,31,[33][34][35][36][37][38][39][40][41][43][44][45][46][47][48][49] of which half were within the first month. 25,30,[33][34][35]38,39,41,45,48,49 Eighteen studies (86%) performed at least three follow-up measures at regular intervals during the first year after surgery.…”
Section: Breast Cancer-related Arm Lymphedemamentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, bilateral measurements can be biased by muscle hypertrophy or weight gain, equally affecting both limbs. The use of techniques that evaluate edema in a direct way, such a bio-impedance spectroscopy and tissue dielectric constant measurements, can assist in the diagnosis of LE, but these techniques have not been validated in the setting of lower limb or genital LE [ 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of breast cancer related lymphedema (BRCL) is reported to vary between 13.50% and 30.00% within two years of surgery, increasing to 30.20% in the fifth year, and 41.10% in the tenth year (Ribeiro Pereira et al, 2017). In Turkey, the incidence of BRCL was up to 26.80% in the first 12 months following surgery (Kamalı Polat et al, 2017).…”
Section: Introductionmentioning
confidence: 99%